INTERNALISASI NILAI KEDISIPLINAN DALAM PEMBENTUKAN KARAKTER SISWA SEKOLAH DASAR - Mita Aulia; Abidinsyah Abidinsyah (Universitas Tribhuwana Tunggadewi, 2026)
This study aimed to describe the internalization of discipline values in developing elementary school students' character through intracurricular, co-curricular, extracurricular, and school culture activities, as well as to identify the supporting and inhibiting factors affecting its implementation. This study employed a qualitative descriptive approach. The participants consisted of the principal, classroom teachers, and students selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings revealed that the internalization of discipline values was implemented through an integrated approach across four educational settings. In intracurricular activities, discipline was fostered through classroom routines, teacher role modeling, and adherence to classroom rules. Co-curricular activities strengthened students' responsibility through collaborative learning and the Projek Penguatan Profil Pelajar Pancasila (P5), while extracurricular activities, particularly Scouting, provided authentic experiences in practicing discipline, leadership, and responsibility. School culture reinforced discipline through the implementation of the 5S (Smile, Greet, Salute, Politeness, and Courtesy) program, flag ceremonies, classroom duties, and thematic school programs. The implementation was supported by strong collaboration between teachers and parents, whereas students' diverse characteristics and limited parental supervision remained the major challenges. The study concludes that integrating discipline values across learning activities and school culture provides a comprehensive strategy for strengthening character education in elementary schools.